2016
DOI: 10.5415/apallergy.2016.6.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, practices on allergic rhinitis of three socioeconomic classes of Filipinos in the National Capital Region

Abstract: BackgroundHealthcare access and usage may vary according to socioeconomic class (SEC). Knowing this variable's effect on patient attitudes, practices, and health seeking behavior allows better understanding of compliance, adherence to treatment, and educational needs on allergic rhinitis (AR).ObjectiveThis study seeks to assess the attitudes and practices on AR of Filipinos in the National Capital Region.MethodsA cross sectional survey of 301 Filipinos, stratified into socioeconomic groups ABC1, C2, and DE, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In general, Filipinos regardless of their symptom severity, are not likely to seek consultation for AR [ 28 ]. The patients who seek consult at a specialty clinic are likely to have complicated or uncontrolled disease that is perceived to require specialized treatment and/or management.…”
Section: Discussionmentioning
confidence: 99%
“…In general, Filipinos regardless of their symptom severity, are not likely to seek consultation for AR [ 28 ]. The patients who seek consult at a specialty clinic are likely to have complicated or uncontrolled disease that is perceived to require specialized treatment and/or management.…”
Section: Discussionmentioning
confidence: 99%
“…The highest allergic rhinitis prevalence was reported as 58.5% in community-based population and increased to 80.3% among children with persistent otitis media and effusion [26,27]. There are reports highlighting that allergic rhinitis impacts the patients' quality of life of allergic rhinitis patients in Southeast Asian region [16,27,28].…”
Section: Allergic Rhinitis Prevalence In Southeast Asiamentioning
confidence: 99%
“…Moreover, several alternative treatment options have been found. For instance, a study in the Philippines found that hydration therapy, fruit juice, and tea are commonly used [ 9 ]. In China, Chinese herbs are widely used as a traditional treatment despite the unknown mechanism of action.…”
Section: Introductionmentioning
confidence: 99%